(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article examines integrative teaching methods in natural science education as a means of overcoming the limitations of traditional subject-based instruction. The study identifies key strategies for effective interdisciplinary integration, including project-based learning, thematic units, and inquiry-based approaches. Through analysis of theoretical frameworks and practical case studies, we demonstrate how integrative methods enhance students’ conceptual understanding, critical thinking skills, and ability to apply knowledge to real-world problems. The paper also discusses implementation challenges and provides evidence-based recommendations for educators